Non-absorbable sutures are associated with lower recurrence rates in laparoscopic percutaneous inguinal hernia ligation. Issue 5 (October 2015) - Grimsby, G.M.; Keays, M.A.; Villanueva, C.; Bush, N.C.; Snodgrass, W.T.; Gargollo, P.C.; Jacobs, M.A.
Summary: Introduction: Laparoscopic hernia repair with percutaneous ligation of the patent processes vaginalis is a minimally invasive alternative to open inguinal herniorrhaphy in children. With the camera port concealed at the umbilicus, this technique offers an excellent cosmetic result. It is also faster than the traditional laparoscopic repair with no differences in complication rates or hospital stay. The goal of this study was to describe a series of consecutive patients, emphasizing the impact of suture materials (absorbable vs. non-absorbable) on hernia recurrences. Methods: A retrospective review was performed of consecutive transperitoneal laparoscopic subcutaneous ligations of a symptomatic hernia and/or communicating hydrocele by 4 surgeons. Patients >  Tanner 2 or with prior hernia repair were excluded. The success of the procedure and number of sutures used was compared between cases performed with absorbable vs. non-absorbable suture. Risk factors for surgical failure (age, weight, number of sutures used, suture type) were assessed with logistic regression. Results: 94 patients underwent laparoscopic percutaneous hernia ligation at a mean age of 4.9 years. Outcomes in 85 (90%) patients with 97 hernia repairs at a mean of 8 months after surgery revealed 26% polyglactin vs 4% polyester recurrences ( p  = 0.004) which occurred at mean of 3.6 months after surgery, Table 1. Repairs performed with non-absorbable suture required only 1 suture more often than those performed with absorbable suture (76% vs 60%, p  = 0.163). Logistic regression revealed suture type was an independent predictor for failure ( p  = 0.017). Weight ( p  = 0.249), age ( p  = 0.055), and number of sutures ( p  = 0.469) were not significantly associated with recurrent hernia. Discussion: Our review of consecutive hernia repairs using the single port percutaneous ligation revealed a significantly higher recurrent hernia rate with absorbable (26%) versus non-absorbable (4%) suture. This finding remained significant in a logistic regression model irregardless of number of sutures placed, age, and weight. Though the authors acknowledge the drawback of the potential for learning curve to confound our data, we still feel these findings are clinically important as this analysis of outcomes has changed our surgical practice as now all providers involved perform this procedure with exclusively non-absorbable suture. We thus suggest that surgeons who perform this technique, especially those newly adopting it, use non-absorbable suture for optimal patient outcomes. Conclusions: Recurrent hernia after laparoscopic percutaneous hernia ligation was significantly lower in repairs performed with non-absorbable suture. Based on this data, we recommend the use of non-absorbable suture during laparoscopic ligation of inguinal hernias in children.